2018
DOI: 10.1002/cbic.201800305
|View full text |Cite
|
Sign up to set email alerts
|

Quick Click: The DNA‐Templated Ligation of 3′‐O‐Propargyl‐ and 5′‐Azide‐Modified Strands Is as Rapid as and More Selective than Ligase

Abstract: The copper(I)-mediated azide-alkyne cycloaddition (CuAAC) of 3'-propargyl ether and 5'-azide oligonucleotides is a particularly promising ligation system because it results in triazole linkages that effectively mimic the phosphate-sugar backbone of DNA, leading to unprecedented tolerance of the ligated strands by polymerases. However, for a chemical ligation strategy to be a viable alternative to enzymatic systems, it must be equally as rapid, as discriminating, and as easy to use. We found that the DNA-templa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Our previous work showed that the CuAAC reaction of 5'-azido and 3'-O-propargyl terminated DNA strands proceeds rapidly using a DNA template to bring together the reactive termini in the presence of a Cu(I) catalyst and 1.5 equivalents (with respect to copper) of a benzimidazole ligand. 62 Using similar conditions with argon degassing, we observed quantitative conversion of the limiting 3'alkyne oligonucleotide fragment after 1 hour of reaction (Figure S2). After the reaction, the triazole-linked tracrRNAs were purified by polyacrylamide gel electrophoresis and characterized by mass spectrometry.…”
Section: Resultsmentioning
confidence: 83%
“…Our previous work showed that the CuAAC reaction of 5'-azido and 3'-O-propargyl terminated DNA strands proceeds rapidly using a DNA template to bring together the reactive termini in the presence of a Cu(I) catalyst and 1.5 equivalents (with respect to copper) of a benzimidazole ligand. 62 Using similar conditions with argon degassing, we observed quantitative conversion of the limiting 3'alkyne oligonucleotide fragment after 1 hour of reaction (Figure S2). After the reaction, the triazole-linked tracrRNAs were purified by polyacrylamide gel electrophoresis and characterized by mass spectrometry.…”
Section: Resultsmentioning
confidence: 83%
“…Our previous analysis of the complementary system lacking the abasic group revealed that the extent of selectivity in the CuAAC chemical ligation reaction stemmed from the intrinsic thermodynamic stability of the different mismatches. [ 24 ] In contrast, T4 DNA ligase exhibited different selectivity patterns, which we attributed to the preference of the enzyme for pyrimidine:purine mismatches even when they exhibited lower stability in the absence of enzyme. This difference in selectivity pattern was also observed for the abasic‐modified CuAAC and T4 DNA ligase systems shown here, which suggested that the thermodynamic stability of the abasic probe:template duplex was not responsible for the T4 DNA ligase selectivity at elevated temperatures.…”
Section: Resultsmentioning
confidence: 98%
“…[ 28–30 ] We observed that the chemical ligation reaction was better at discriminating than the enzyme catalyzed reaction in the recommended temperature window (near or below the T m of the matched system and above that of the mismatched system). [ 24 ] To see whether this selectivity of the CuAAC ligation also increased at higher temperatures, we performed the same type of ligation experiments with a 5′‐azido thymidine or 5′‐azido abasic terminus (Figure 4). At temperatures above the T m of the 5′‐azido thymidine and 5′‐azido abasic probe:template duplexes (29 °C and 23 °C, respectively, Table 1), the overall yield decreased significantly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] Owing to this reactivity, azido modifications are often inserted into oligonucleotides enzymatically, [14,15] or chemically after solid phase ON synthesis has been concluded. [16][17][18] H-phosphonate or phosphotriester chemistry was also used instead of the phosphoramidite approach for the synthesis of azido-modified oligonucleotides, [19][20][21] or synthesis of 3'-terminal azido modified ODNs was conducted in reverse orientation from 5' to 3'-end. [10] Yet, there have been reports on the chemical synthesis of azido modified ONs by the standard phosphoramidite strategy.…”
Section: Introductionmentioning
confidence: 99%